The Effect Of Price Perception And Promotion On Purchasing Decisions Of Ice Cream Aice At Delapan Belas Kiarajangkung Tasikmalaya Stores (Survey on sales of ice cream Aice at Delapan Belas Kiarajangkung Stores) - Neng Siti Ambariyah; Depy Muhamad Pauzy; Ari Arisman (Penerbit Jurnal Indonesia, 2023)
This purpose of this study to determine the effect of price perception and promotion on purchasing decisions of ice cream Aice at Delapas Belas Kiarajangkung Tasikmalaya Stores (Survey on sales of ice cream Aice at Delapan Belas Kiarajangkung Stores). The method used is a quantitative method with a research sample of 100 respondents who are customer ice cream Aice at Delapan Belas Kiarajangkung Stores. The data is used primary data and secondary data. The analitycal tool in this research is multiple regression using by SPSS version 25. The result showed that simultaneously price perception and promotion has a significant influence on purchasing decisions. Parrtially price perception has a significant influence on purchasing decisions. Parrtially promotion has a significant influence on purchasing decisions.